The effects of hypothyroidism on the proximal femoral physis in miniature swine. Issue 12 (23rd August 2013) - Tank, Jason C.; Weiner, Dennis S.; Jacquet, Robin; Childs, Dylan; Ritzman, Todd F.; Horne, Walter I.; Steiner, Richard; Morscher, Melanie A.; Landis, William J.
ABSTRACT: As a potential means of comparing hypothyroidism in humans, this work intended to establish a defined hypothyroid state in immature miniature swine and evaluate specific molecular, cellular, and extracellular responses of their growth plates. Two male, 11‐week‐old Sinclair miniature swine were given 6‐propyl‐2‐thiouracil (PTU) in their water and two other like animals (controls) were provided water without PTU. Blood levels of thyroid stimulating hormone (TSH), triiodothyronine (T3), and thyroxin (T4) were monitored weekly. At 25 weeks of age, the hind limb proximal femoral physes were harvested and divided into portions for histology and reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR) analysis. Compared to controls, swine administered PTU exhibited increased TSH and decreased T3 and T4 serum levels during the study period, features consistent with a hypothyroid state. Compared to controls, hypothyroid swine exhibited structurally altered physes and demonstrated significantly decreased gene expression of aggrecan ( p < 0.05) and type X collagen ( p ≤ 0.1). This is the first hypothyroid model established in miniature swine and represents a potentially important advance for understanding the condition in humans, in which, like this swine model, there are changes critical to growth plate molecular biology, biochemistry and structure. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1986–1991, 2013